2021
DOI: 10.1002/hbe2.256
|View full text |Cite
|
Sign up to set email alerts
|

Association between mobile phone screen time and depressive symptoms among college students: A threshold effect

Abstract: College students today suffer more than ever from depressive symptoms. This web‐based survey collected both subjective self‐reported and objectively measured mobile screen time from smartphones' screen time reporting feature from 426 and 175 college students, respectively. Depressive symptoms were measured by the 10‐item Center for Epidemiologic Studies Short Depression Scale. Logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (95% CI), adjusting for gender, race/eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
(84 reference statements)
0
8
0
1
Order By: Relevance
“…Social media also provides a platform where idealistic versions of the self are often selectively portrayed, hence offering abundant opportunities for social comparison and as a result triggering anxiety, loneliness, depression, sensitivity to social exclusion, poor academic performance, and overall poor wellbeing [1,8,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Uneasiness is often experienced as a result of glancing at a stream of social network posts, photos, status updates, and videos featuring the fun that peers are having, thus evoking a general feeling of "missing out" [25,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Social media also provides a platform where idealistic versions of the self are often selectively portrayed, hence offering abundant opportunities for social comparison and as a result triggering anxiety, loneliness, depression, sensitivity to social exclusion, poor academic performance, and overall poor wellbeing [1,8,14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Uneasiness is often experienced as a result of glancing at a stream of social network posts, photos, status updates, and videos featuring the fun that peers are having, thus evoking a general feeling of "missing out" [25,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Oman has high internet penetration, and being a high middle-income country, most new gadgets for communications are widespread among different population strata. A previous study reported that students who spent more than 5.72 h on mobile phone screening had a significantly higher risk of depressive symptoms than those less than 3.05 h (Rosenthal et al , 2021). There is evidence to suggest that informational technology has triggered the increased frequency of HLID (Hamasaki et al , 2021), and it is likely that emerging technology for communication has invariably acted as the catalyst for increasing the frequency of HLID (Yung et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Depression also causes participants to reduce their interaction with friends and family, and call-related features can play a role in characterizing this behavior. The screen time of individuals has been seen to be a reflection of mood, as explored in an earlier study [ 48 ]. Feature importance helps narrow down the exact features that contributed to modeling.…”
Section: Discussionmentioning
confidence: 99%